An Examination of the Expected Rate of Return (ERR) on Pension Assets and Asset Allocation in UK Occupational Defined Benefit Pension Schemes. - Akele, Osaretin (2010)
This research investigates the usefulness of the Expected Rate of Return (ERR) on pension assets using a sample of 54 companies from the FTSE 100 over 5 years (2005-2009). Firstly, the correlation between the ERR, as reported in the financial statements and the asset allocation of the pension portfolio, measured as the percent invested in equities (%Equity) is examined. The results obtained from the correlation analysis, indicate that the ERR and %Equity are related but this relation is moderate. Secondly, a panel data analysis is used to examine which is better at predicting the actual return on pension assets, asset allocation (%Equity) or the ERR. The empirical evidence obtained showed that the %Equity is positively correlated with the actual returns on pension assets, while the ERR is negatively correlated with the actual return on pension assets. The empirical results obtained in this research suggest that although it does not matter which is disclosed, the ERR or %Equity. The %Equity is more useful in predicting the actual return on pension assets compared to the ERR. Therefore financial statement users, who want to predict the cost of future pension benefits should focus more on asset allocation (%Equity) than the ERR, as it is more useful. This research follows the study on private pensions in the United States by Amir and Benartzi (1998) and that of public pensions by Eaton and Nofsinger (2001).